Estratégia nas cadeias do agronegócio como ferramenta indutora do desenvolvimento regional: proposição de modelo de análise e aplicação na cadeia da soja em Toledo (PR) - Gruber, Rafael Ricardo (2009)
This study analyses strategically the regional development together with the economical viability subject. An analysis model is proposed, inspired on SWOT and BCG matricial analysis, bringing concenpts from business strategy, creating tolls based on a theorical structure about regional development and economical viability analysis. This model is applied on soybean chain in Toledo-PR. Forty-eight opportunities are identified along the chain, and seven are analysed in details. The results show in a grafical analysis the position of each opportunity studied, crossing regional development and economical viability indicators. Among the opportunites studied, the ones considered strategical for the region are: agricultural machinery and implements industry, fertilizer industry; and margarine and vegetable oil industry. It is also presented the analysis model proposed, that can be used in researches in future.